Associations and Implications of Low Health Literacy in Parkinson's Disease. Issue 3 (14th December 2015) - Fleisher, Jori E.; Shah, Krunal; Fitts, Whitney; Dahodwala, Nabila A.
Abstract: Background: Low health literacy (HL) indicates a limited ability to understand and use basic information to make appropriate health care decisions. Whereas low HL is associated with higher morbidity, mortality, and health care costs in multiple chronic conditions, little is known about HL and its associations in Parkinson's disease (PD). Methods: This was a cross‐sectional study of nondemented adults with PD participating in the National Parkinson Foundation Parkinson's Outcomes Project at the University of Pennsylvania. Subjects were administered two brief HL assessments—the Rapid Estimate of Adult Literacy in Medicine‐Short Form (REALM‐SF), a word‐recognition test, and the Newest Vital Sign (NVS), a test of literacy, numeracy, and understanding of health information—as well as demographic and clinical questionnaires. Adverse outcomes included falls in the 3 months preceding the study visit and hospital admissions, emergency room visits, infections, or injuries in the preceding year. Caregiver burden was measured using the Multidimensional Caregiver Strain Index. Results: A total of 168 subjects completed both HL screens (mean, 65.8 years; 65.5% male; 65.2% H & Y stage 2). Using the REALM‐SF, 97.6% of subjects had adequate HL. Using the NVS, however, 29.8% had low HL, which was associated with older age, lower education, male sex, greater disease severity, and poorer cognition. Low HL was associated with hospital admission and increased caregiver burden. Conclusions: Low HL is common and associated with greater caregiver burden and a higher likelihood of hospitalization in patients with PD. Because HL is associated with both disease severity and adverse outcomes, it may be an important, modifiable contributor to morbidity.